New apotirucallane-type triterpenoids from Chisocheton paniculatus - Zhang, Feng (Springer Berlin Heidelberg, 2012)
Two new apotirucallane triterpenoids, namely chisiamols G (1) and H (2), featuring a 21,23-lactone, together with five known triterpenoids, were isolated from the twigs of Chisocheton paniculatus. The structures of the new compounds were elucidated on the basis of spectroscopic and chemical methods. [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available for this article at 10.1007/s13659-012-0065-5 and is accessible for authorized users.